IDENTIFICATION OF POTENTIAL INHIBITORS OF Α-GLUCOSIDASE ENZYME FROM WITHANIA COAGULANS AND SWIETENIA MACROPHYLLA USING GC-MS PROFILING, IN SILICO MOLECULAR DOCKING AND MOLECULAR DYNAMICS SIMULATION STUDIES - ROSLIN ELSA VARUGHESE; GAYATHRI DASARARAJU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Diabetes mellitus, a global health concern, is characterized by persistently elevated blood glucose levels, which can lead to damage in various organs over time. The enzyme α-glucosidase plays a critical role in carbohydrate digestion by hydrolyzing complex polysaccharides into absorbable monosaccharides. Inhibition of this enzyme helps attenuate postprandial hyperglycemia by delaying carbohydrate breakdown and absorption. In the present study, we aimed to identify potential natural α-glucosidase inhibitors from the ethyl acetate and ethanol extracts of two medicinally essential plants: Withania coagulans and Swietenia macrophylla. Methods: Gas chromatography–mass spectrometry analysis was carried out to identify the compounds, which were subjected to virtual screening against α-glucosidase using AutoDock Vina. The top three ligands from each extract were further validated through re-docking using AutoDock 4.2, allowing for detailed analysis of binding energies and interactions within the enzyme’s active site. The top lead compounds from docking results were subjected to molecular dynamics (MD) simulation studies. Results: Cholest-5-ene-3,16,22,26-tetrol (from W. coagulans) and 1,5-Anhydro-4,6-O-benzylidene-D-glucitol (from S. macrophylla) exhibited better binding energies of –6.66 and –5.64 kcal/mol, respectively, compared to the reference inhibitor acarbose (–4.27 kcal/mol). These lead complexes were further subjected to MD simulations to assess the conformational stability and structural dynamics of the enzyme-compound complexes. The average root-mean-square deviation for the last 50 ns of enzyme-lead complexes was found to be 0.14 and 0.16 nm. Conclusion: The identified compounds show good binding energy and maintain the hydrogen bond and hydrophobic interactions with active site residues of the enzyme. This study highlights the potential of plant-derived phytochemicals as promising α-glucosidase inhibitors and provides a computational foundation for their further in vitro and in vivo evaluation in the management of diabetes mellitus.